2016
DOI: 10.1007/s12088-016-0567-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Localization of Wolbachia in Thrips palmi Karny (Thysanoptera: Thripidae)

Abstract: Thrips palmi Karny is a globally distributed polyphagous agricultural pest. It causes huge economic loss by its biological behaviors like feeding, reproduction and transmission of tospoviruses. Since T. palmi shows close morphological similarities with other thrips species, we employed mitochondrial cytochrome oxidase 1 (mtCO1) gene as a molecular marker. BLAST analysis of this sequence helped us to identify the collected specimen as T. palmi. We observed the female to male ratio of about 3:1 from collected sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This bacterium can eliminate males, turn them into females, sterilize uninfected females or behave as a mutualistic symbiont 113 . Wolbachia has been detected both in arrhenotokous and thelytokous thrips species 108 , 109 , 111 although the frequency of this reproductive manipulators in Thysanoptera is unknown. The absence of Wolbachia , identified by conventional PCR, has been shown for three thrips: Frankliniella occidentalis 108 , Thrips tabaci 108 , 114 and Heliothrips haemorrhoidalis 115 .…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium can eliminate males, turn them into females, sterilize uninfected females or behave as a mutualistic symbiont 113 . Wolbachia has been detected both in arrhenotokous and thelytokous thrips species 108 , 109 , 111 although the frequency of this reproductive manipulators in Thysanoptera is unknown. The absence of Wolbachia , identified by conventional PCR, has been shown for three thrips: Frankliniella occidentalis 108 , Thrips tabaci 108 , 114 and Heliothrips haemorrhoidalis 115 .…”
Section: Discussionmentioning
confidence: 99%
“…tabaci [25,29]. Wolbachia has been reported in other thrips species such as Echinothrips americanus , Gynaikothrips ficorum , Suocerathrips linguis [29], Thrips palmi [63] and Hoplothrips carpathicus [42] but their role in T . tabaci is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Pantoea ananatis and Pantoea agglomerans were detected in the Thrips tabaci gut by Dutta et al [20]. Other studies have demonstrated the presence of Wolbachia in Franklinothrips vespiformis [21], Scirtothrips perseae [22], Echinothrips americanus, Suocerathrips linguis, Gynaikothrips ficoru, Hercinothrips femoralis and Parthenothrips dracaenae [23], Thrips palmi [24], and Hoplothrips carpathicus [25]. Finding the genus Wolbachia in a pest species is important because it increases the potential for the pest's biological control.…”
Section: Introductionmentioning
confidence: 95%